"PRICE, PRODUCT QUALITY AND PROMOTION ON PURCHASE DECISIONS" (EMPIRICAL STUDY ON CONSUMERS IN AMBON CITY) - Sipakoly, Selly (Dinasti International Journal of Management Science, 2022)
This study aims to empirically examine the influence of price factors on purchasing decisions, the influence of product quality factors on purchasing decisions and the influence of promotional factors on consumer purchasing decisions of Cap Nona Sweetened Condensed Milk in Ambon City. The type of research is empirical with the sampling technique used is purposive sampling. The analysis technique is multiple linear regression analysis, where the hypothesis test uses the t-statistical test to test the partial regression coefficients and the F-statistical test to test the effect together or simultaneously with a confidence level of 0.05 or 5%. The test results show the price variable (X1) has a positive and significant effect on the purchasing decision variable. This is evidenced by the results of statistical tests which show the coefficient value of 0.192 with a significant value of 0.01 below the 0.05 level of significance. The product quality variable (X2) has a positive and significant effect on the purchasing decision variable. This is evidenced by the results of statistical tests which show a coefficient value of 0.191 with a significant value of 0.00 below the significant level of 0.05. The promotion variable (X3) has no significant effect on the purchasing decision variable. This is evidenced by the results of statistical tests which show the coefficient value of 0.134 with a significant value of 0.28 above the significant level of 0.05.